Fintech Perceived Usefulness, Ease Of Use Among Consumers And Its Effect On Satisfaction And Continuous Usage: An Impractical Study On STC Pay And Apple Pay In Saudi Arabia’s Retail Sector (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2022)
This paper study the effect of perceived ease of use and perceived usefulness on customers' satisfaction with FinTech and its impact on the continuous usage of FinTech among Saudi customers. A survey was conducted using an electronic and self-administered questionnaire. A total of 250 questionnaires were distributed among Saudi users of FinTech services. The valid questionnaires were 121; they were tested using SPSS and AMOS. This study examines the following factors: perceived ease of use and perceived usefulness as independent factors and included satisfaction as a mediator factor to study how it mediates the relationship between the independent factors and the dependent factor. The continuous usage of FinTech was the dependent factor. Results reveal that both perceived ease of use and perceived usefulness have a significant effect on customer satisfaction, and the three variables have a significant positive effect on the continuous usage of FinTech among Saudi customers. Conclusion, study limitations, and future studies were provided.